2016
DOI: 10.1055/s-0042-112816
|View full text |Cite
|
Sign up to set email alerts
|

The Adrenocortical Response to Synthetic ACTH Following a Trek to High Altitude

Abstract: Background: Gradual ascent to high altitude is typically associated with reduced resting aldosterone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…We have previously shown that with pharmacological stimulation of adrenal steroidogenesis using synacthen at HA, the cortisol response remains intact compared to SL but that the aldosterone response is subdued. 32 Again, we had suspected that this reflects reduced activity of CYP11B2, but our subsequent analysis does not support this.…”
Section: Discussionmentioning
confidence: 74%
“…We have previously shown that with pharmacological stimulation of adrenal steroidogenesis using synacthen at HA, the cortisol response remains intact compared to SL but that the aldosterone response is subdued. 32 Again, we had suspected that this reflects reduced activity of CYP11B2, but our subsequent analysis does not support this.…”
Section: Discussionmentioning
confidence: 74%